End of Life Care for People with Dementia : a Person-Centred Approach. - Murna Downs; Laura Middleton-Green; Jane Chatterjee; Sarah Russell (Jessica Kingsley Publishers, 2016)
People with dementia need increasingly specialised support as they approach the end of life, and so too do their families and the professionals who work with them. This book describes not only what can be done to ensure quality of life for those with the illness, but also how best to support those who care for them throughout this difficult period.